What, How and What for – on the Relation Between Form and Function as Illustrated by Haiku - Tabakowska, Elżbieta (Poznańskie Studia Slawistyczne, 2017)
The paper addresses the problem of mutual relation between form and function as exemplified by haiku. Focusing upon the structure of haiku conducive to epiphany, it discusses some general aspects, independent of the differences between Eastern and Western varieties of the form. The “literariness” of the genre is demonstrated with reference to dimensions of imagery (as defined in Langacker’s model of cognitive grammar), and to the strongly metonymic character of haiku. Finally, some shortcomings of “Polish haiku” are shown as a function of its culture-bound untranslatability.